SYSTEMATIC LITERATURE REVIEW AND SIMPLE META-ANALYSIS: THE EFFECT OF ACCOUNTABILITY ON LOCAL GOVERNMENT FINANCIAL MANAGEMENT - Pramandyah Fitah Kusuma (Income, 2026)
This study aims to synthesize empirical findings regarding the influence of accountability on local government financial management through a Systematic Literature Review (SLR) and a simple meta-analysis. A total of 10 primary studies (2020-2025) from various databases were analyzed. The results of the qualitative synthesis indicate a shift in research focus from compliance accountability to performance-based and digital accountability. Quantitatively, accountability was found to have a positive and significant influence on the quality of local financial management, mediated by variables such as transparency and internal control systems. The novelty of this study lies in the mapping of accountability and financial management indicators, as well as the identification of research trends leading to technology integration. These findings have important implications for the formulation of more effective and accountable local financial governance policies